To connect or not to connect: Visitor preferences for Wi-Fi and cellular network service at a national park. Issue 1 (2021) - Peterson, Brian A.; Fefer, Jessica P.; Sharp, Ryan L.; Brunson, Michael M.; Skibins, Jeffrey C.
Abstract: Worldwide mobile devices have become ubiquitous including for visitors to parks and protected areas. Wireless communication technologies, such as Wi-Fi access and cellular network service, are also common but not all parks and protected areas provide these services. Wireless communication technologies could alter the visitor experience, however little is known about visitor preferences for Wi-Fi access and cellular network service nor about experiential outcomes of mobile device usage in natural settings. Therefore, the purpose of this research was twofold: to understand visitor preferences for Wi-Fi access and cellular network service, and experiential outcomes of mobile device usage. The study site for this research was Shenandoah National Park ( n = 1442). Using k -means clustering analysis, data were clustered into visitor groups and statistically compared to gain insight into patterns of responses. Visitors mostly reported neutral preferences for Wi-Fi access and cellular network service except for cell service park-wide in all national parks was reported as important. One group of visitors ( n = 239) reported that these technologies were unimportant and mobile device usage diminishes their experience. Analysis was also conducted to investigate preferences across age, which showed older demographics reported both cell service park-wide and cell service park-wide in all national parks as important. This information is relevant for management decisions regarding wireless communication technologies access and availability within parks and protected areas.